406. Achievement of Clinical Isavuconazole (ISA) Serum and Plasma Drug Concentrations in Two Patients With Isavuconazonium Capsules Administered via Nasogastric Feeding Tube (NGT). (26th November 2018) - McCreary, Erin K; Borlagdan, Jared; Andes, David R; Kinn, Patrick; Schulz, Lucas T; Lepak, Alexander J
Abstract: Background: Isavuconazole is a broad-spectrum antifungal available in both intravenous (IV) and oral capsule formulations for the treatment of invasive aspergillosis and mucormycosis. Oral administration can be challenging as FDA prescribing information states capsules should not be chewed, crushed, dissolved, or opened. We describe the first two cases, to our knowledge, of patients who received isavuconazonium capsules sprinkled via NGT with concomitant therapeutic drug monitoring (TDM). Methods: All ISA serum and plasma assays resulted from January 1, 2016 to February 1, 2018 at a tertiary academic medical center were assessed. Isavuconazole assays were performed by Viracor Eurofins, Inc. using liquid chromatography-tandem mass spectrometry. Retrospective chart review was performed for all patients. Assay results from patients receiving whole capsules by mouth (PO) were compared with NGT. Results: Nineteen unique patients had 33 ISA assays during the study period. Two patients received capsules via NGT. The first patient was a 59-year-old female treated empirically for fungal rhinosinusitis who received 5 days of IV therapy prior to switching to NGT. Trough ISA levels on days 11 and 23 were 1.9 and 1.5 μg/mL, respectively. The second patient was a 66-year-old male treated for presumed invasive pulmonary aspergillosis who received 7 days of NGT therapy; trough level on day 8 was 2.9 μg/mL. Both patients received continuous tube feedings and were liver transplant recipients. In comparison, trough concentrations in the PO group ( N = 17) ranged from 1.1 to 8.0 μg/mL (3.79 ± 1.68). All patients received FDA-approved loading and maintenance dosing. Conclusion: Patients receiving isavuconazonium via NGT (opened sprinkled capsules) achieved clinically detectable serum ISA levels in a therapeutic range comparable to patients receiving PO. This study provides the first evidence that enteral routes other than PO may be effective for isavuconazonium administration. While the establishment of a trough concentration threshold predicting ISA therapeutic efficacy remains to be determined, TDM in patients receiving capsules by an enteral route other than PO may play an important role. Disclosures: D. R. Andes, Astellas: Consultant and Grant Investigator, Consulting fee and Grant recipient